RESTORATIVE JUSTICE: SAAT HUKUM MENDENGARKAN KORBAN - Nahor, T. Banjar (LPPM STIH Awang Long, 2025)
This paper explores restorative justice as a response to the limitations of the conventional criminal justice system, which has traditionally focused more on punishing offenders than on restoring victims. Restorative justice shifts the paradigm by placing victims at the center of the legal process, allowing their voices to be meaningfully heard. This study employs a normative juridical method with a qualitative approach, analyzing legal frameworks, theories, and current practices in Indonesia. The findings indicate that while policies such as the Prosecutor’s Regulation No. 15 of 2020 and the Indonesian National Police Regulation No. 8 of 2021 have opened pathways for restorative justice, practical challenges remain—ranging from institutional resistance and public misunderstanding to potential misuse. Thus, there is a pressing need to strengthen the justice system’s capacity to become more empathetic and victim-centered, emphasizing healing over retribution. impact on the contractor or individual/private legal entity.